Sanksi Pidana Terhadap Pembuat Stiker Prnografi di Media Komunikasi Whatshap - Putu Bagus Dio Adinatha; Anak Agung Sagung Laksmi; I Made Minggu Widyantara (Warmadewa Press, 2021)
The spread of pornographic content is not only spread through access to pages on the internet website but is spread through various platforms, one of which is communication media. Currently, the majority of people from various age groups and economies are very familiar with online communication media. This study aimed to examine the legal arrangements against pornographic sticker makers in WhatsApp communication media and examine criminal sanctions against pornographic sticker makers in WhatsApp communication media. This type of research used normative law with a Legislative and Conceptual approach. Sources of legal materials consisted of primary, secondary, and tertiary sources of legal materials. It could be obtained through an inventory or tracing technique of relevant legal materials and then classified or grouped and documented, recorded, quoted, summarized. The results of the study showed that the legal arrangements for making pornographic stickers on WhatsApp communication media are regulated in the ITE Law (Electronic Information and Transactions) Law No. 11 of 2008, the Criminal Code (KUHP), and the Pornography Law - Law No. 44 of 2008 which can ensnare the perpetrators of pornographic sticker makers on WhatsApp communication media. Criminal sanctions against pornographic sticker makers on WhatsApp communication media, any person who intentionally and without rights spreads information that aims to cause hatred or hostility to certain individuals and/or community groups based on ethnicity, religion, race, and intergroup (SARA), will be subject to criminal sanctions with a maximum imprisonment of six years or a maximum fine of Rp. 1 Billion.